2007
DOI: 10.1590/s0004-282x2007000700027
|View full text |Cite
|
Sign up to set email alerts
|

Impacted cisterna magna without syringomyelia associated with lancinating headache, throbbed nuchal pain and paraparesis treated byposterior fossa decompression

Abstract: -A 29-year-old woman with acute lancinating headache, throbbed nuchal pain and subacute paraparesis underwent brain MRI in supine position that depicted: the absence of the cisterna magna, filled by non herniated cerebellar tonsils and compression of the brain stem and cisternae of the posterior fossa, which are aspects of the impacted cisterna magna without syringomyelia and without hydrocephalus. During eight days, pain was constant and resistant to drug treatment. Osteodural-neural decompression of the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The au-thors named the full cisterna magna as "tight cisterna magna" and designated Iskandar's description as "Chiari 0 malformation". Gonçalves da Silva et al 29 named this type of cisterna magna as "impacted cisterna magna".…”
Section: Discussionmentioning
confidence: 99%
“…The au-thors named the full cisterna magna as "tight cisterna magna" and designated Iskandar's description as "Chiari 0 malformation". Gonçalves da Silva et al 29 named this type of cisterna magna as "impacted cisterna magna".…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Iskandar and Tubbs et al used "Chiari zero malformation" to characterize this kind of syringomyelia disorder and advised craniovertebral decompression (CVD) as the surgical modality (8, 9,16,17). There is a very limited number of papers on the "Chiari zero malformation", and there is a query about the truth of this pathology (8, 9,10,14,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…This kind of "up and down CM" was observed also in cases without SM. 19,21 Iskandar et al 7 reported on five cases of SM, in which the cisterna magna was filled with the cerebellar tonsils. In all five cases there was clinical improvement after posterior fossa decompression and a marked reduction in the size of the syrinx.…”
Section: Discussionmentioning
confidence: 99%
“…Spastic tetraparesis and paraparesis are frequently described in patients with BI and/or CM and SM. [9][10][11][12][13][14][15][16][17][18][19] In our five cases SM was absent, despite an evident obstruction of the CSF flow in the posterior fossa caused by the blockage of the foramen of Magendie by a membrane in four cases and the cerebellar tonsils in one case. This finding lead us to hypothesize about whether SM would not develop in the presence of foraminal obstruction, even knowing that the obstruction of the CSF flow in the posterior fossa is considered to be the prime condition for its development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation